Code Swithing Used By Livy Renata On Denny Sumargo Youtube Channel - Ni Komang Citra Pradnyadari; Yana Qomariana (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research is analyzing types of code switching used by Livy Renata on Denny Sumargo Youtube Channel. In this research, the researchers analyzed three types of code switching, there are: estrasentential code switching, intersentential code switching, intrasentential code switching. Qualitative method research based on content analysis was watching the video, listening the audio, and identifying the code switching. After analyzing the data, the researchers found 38 data and the researchers got a result such as: extrasentential code switching have 6, intersentential code switching have 12, intrasentential code switching have 20.